The Relationship of Knowledge and Attitude to The Behavior of Using Celery as An Antihypercholesterolemia at The Gandus Health Center in Palembang - Nia Savitri Tamzil; Debby Handayati Harahap; Evi Lusiana; Nita Parisa; Ayeshah Augusta Rosdah; Syarinta Adenina; Desi Oktariana (Sriwijaya Journal of Medicine, 2024)
Efforts to lower cholesterol levels can be made using traditional medicine. The better a person's knowledge and attitude towards traditional medicine will influence his actions in choosing medicine. This study aims to determine the relationship between knowledge and attitudes regarding traditional medicine on the behavior/actions of choosing celery to treat hypercholesterolemia in the community around the Gandus Health Center, Palembang. Analytical observational research with a cross-sectional design has been carried out at the Gandus Palembang Health Center from 13 to 20 September 2023. 30 respondents met the inclusion criteria. There are still many (43.3%) respondents who have poor knowledge about the use of herbs as anti-hypercholesterolemia, especially celery, while 30% of respondents with a negative attitude towards choosing traditional medicine were found. Based on statistical analysis, the results showed that there was an insignificant relationship between knowledge and behavior (PR = 1.500 (IK95% 0.325 – 6.918); p = 0.896). However, there is a significant relationship between attitudes and behavior (PR = 21.00 (95% CI 2.868 – 153.754); p = 0.002). A person's attitude towards traditional medicine is related to their behavior/actions in choosing celery for the treatment of hypercholesterolemia.